Distribution and structure of lesions in the gills of Atlantic salmon, Salmo salar L., affected with amoebic gill disease - Adams, MB; Nowak, BF (Journal of Fish Diseases, 2001)
Gills of Atlantic salmon, Salmo salar L., with amoebic gill disease (AGD), were analysed by routine histology to identify lesion morphology and distribution patterns. Numbers of lesions occurring dorsally, medially and ventrally in the gill filaments were recorded as was lesion size, proximity to the gill arch and the degree of pathological severity involved. The mean number of lesions and pathological severity in the dorsal region of the second left gill arch were significantly higher than that found ventrally (P < 0.01). There were no significant differences between gill regions in lesion size or proximity of lesions to the gill arch. Serially sectioned lesions revealed interlamellar cysts to be spherical to ovate in shape and fully enclosed within a wall of epithelium. Small to medium size cysts sometimes contained necrotic amoebae. Inflammatory cells, morphologically identified as neutrophils and macrophages, were occasionally seen infiltrating medium sized cysts. Larger cysts were mostly clear of any cellular debris.